2018
DOI: 10.31047/1668.298x.v1.n35.20458
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of essential oil from Eucalyptus globulus against Aphis nerii (Boyer) and Gynaikothrips ficorum (Marchal)

Abstract: Aphids and thrips are very important pest species of many greenhouse and field plants in the world. In recent years, there have been attempts to identify plants for their insecticidal property with a view to find out suitable alternatives to the indiscriminate use of chemical pesticides, which are a risk for human health and the environment. The aim of this work was to evaluate the insecticidal effect of Eucalyptus globulus Labill essential oil (EO) against Aphis nerii Boyer de Fonscolombe (Hemiptera: Aphidida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The contact toxicity of the essential oil of Eucalyptus globulus Labill. against A. nerii has been reported by Russo et al [ 53 ]. Although this is the only previous study to investigate the susceptibility of A. nerii to a plant essential oil, its findings confirm the results of the present study about the possibility of A. nerii management through plant essential oils.…”
Section: Discussionmentioning
confidence: 93%
“…The contact toxicity of the essential oil of Eucalyptus globulus Labill. against A. nerii has been reported by Russo et al [ 53 ]. Although this is the only previous study to investigate the susceptibility of A. nerii to a plant essential oil, its findings confirm the results of the present study about the possibility of A. nerii management through plant essential oils.…”
Section: Discussionmentioning
confidence: 93%
“…Essential oils are complex mixtures of volatile organic substances, consisting of oxygenated compounds and hydrocarbons, such as sesquiterpenes and monoterpenes, were widely applied in food, perfumes, toiletries, chemical additives, medicine and pharmaceutical science . Many plant essential oils and their major constituents exhibit a wide range of biological properties, such as insecticidal, antibacterial, antifungal, spasmolytic, and so on . Due to the great value, the development of essential oils from plants and evaluation on their activities is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus citriodora has exhibited noteworthy effects against Myzus persicae Sulzer, a pest that impacts citrus trees [ 34 ]. In a recent study conducted by Pathak et al [ 35 ], both Eucalyptus globulus and its constituent, 1,8-cineole, demonstrated high efficacy against A. fabae , resulting in a mortality rate of 81.08 ± 6.2 % after 24 h. Similarly, Russo et al [ 36 ] reported a 100 % mortality rate after 24 h for Eucalyptus globulus EO when used against A. nerii .…”
Section: Resultsmentioning
confidence: 99%